Trends in perioperative outcomes of hospitals performing major cancer surgery. Issue 4 (21st August 2018) - Liu, Jason B.; Berian, Julia R.; Liu, Yaoming; Ko, Clifford Y.; Weber, Sharon M.
Abstract : Background and Objectives: Cancer surgery outcomes at National Cancer Institute‐designated cancer centers (NCI‐CCs) have been shown to vary, and have not been uniformly better than outcomes among non‐NCI‐CCs. We aimed to assess whether NCI‐CCs have improved their short‐term outcomes over time and whether variation across these centers has changed. Methods: Patients who underwent colectomy, esophagectomy, hepatectomy, pancreatectomy, and proctectomy for cancer were identified from the 2010 to 2016 American College of Surgeons' National Surgical Quality Improvement Program registry. Hospital trends in risk‐adjusted, smoothed observed‐to‐expected ratios were assessed to evaluate improvement and variation in perioperative complications, stratified by NCI‐CC status. Results: Complications occurred in 18.8% of 204 732 patients who underwent major cancer operations at 645 hospitals, and complications occurred in 19.9% of 60, 903 patients at 54 NCI‐CCs studied. More NCI‐CCs than non‐NCI‐CCs improved over the period (85.2% vs 58.4%, P < 0.001; relative risk [RR] 1.46, 95% confidence interval [CI], 1.28‐1.66); this remained significant after adjusting for years of participation (RR 1.33, 95% CI, 1.17‐1.51). Variation in performance remained unchanged over time. Conclusion: NCI‐CCs were detected to have improved over a contemporary seven‐year period and to have improved more than non‐NCI‐CCs. However, NCI‐CCs do not uniformly outperform non‐NCI‐CCs, and variation in perioperative outcomes remains, warranting continued quality improvement efforts targeting cancer‐specific operations.